2018
DOI: 10.1055/s-0038-1667285
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Septic Arthritis of Lumbar Facet Joint with Epidural Abscess, and Bacterial Meningitis Caused by Methicillin-Sensitive Staphylococcus aureus

Abstract: Septic arthritis of the facet joint is an extremely rare condition, even more in young immunocompetent patients. There have been approximately only 40 cases of this entity reported worldwide. Here, the authors present a 16-year-old male patient with lower back pain, fever, and cephalea. Blood cultures and cerebrospinal fluid analysis confirmed methicillin-sensitive Staphylococcus aureus infection, and magnetic resonance imaging showed septic arthritis of the lumbar left facet joint L3 and epidural abscess. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Lee et al 1 reported a case of spinal epidural abscess complicated by facetal septic arthritis treated by antibiotic beads. As far as we know, the only case reported regarding LFA complicating meningitis is by Maldonado-Morán et al 3 . The patient was a 16-year-old adolescent boy without any neurological deficit and recovered after receiving only antibiotics without surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lee et al 1 reported a case of spinal epidural abscess complicated by facetal septic arthritis treated by antibiotic beads. As far as we know, the only case reported regarding LFA complicating meningitis is by Maldonado-Morán et al 3 . The patient was a 16-year-old adolescent boy without any neurological deficit and recovered after receiving only antibiotics without surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) scans clearly demonstrate the presence of joint effusion and paraspinal muscle edema. MRI with gadolinium contrast is the imaging modality of choice because the extent of facetal collection can be better visualized and helps in delineating soft-tissue involvement such as paraspinal and epidural abscess 3 . Technetium 99 bone scintigraphy is 100% sensitive and can detect facet infections as early as 3 days from the onset of symptoms; however, it lacks specificity 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation